Comparison of mechanical and structural performance of fire-resistant steels at elevated temperatures. (February 2023) - Kumar, Waibhaw; Sharma, Umesh Kumar; Pathak, Prashant
Abstract: Advancements in the steel-manufacturing process led to the development of the low-alloyed Cold-Formed Structural Steel (CFSS) characterizing the ability to sustain higher strength at high temperatures. This paper evaluates the high-temperature performance of low-alloyed Fire-Resistant (FR) CFSS sections having 0.1 % Mo content (YSt-355FR (0.1 % Mo)), which is recently developed an enhanced version of YSt-355 CFSS. The high-temperature tensile tests were done on 87 steel specimens having a holding period of 120 min. The steel specimens were cut out from the different (corner, welded, and non-welded) regions of the steel tube to study the material homogeneity. The obtained tensile curves indicate that the mechanical properties obtained from various regions of the hollow steel cross-section were found to be different. The metallurgical composition, mechanical properties, and structural performance of tested steel (YSt-355FR (0.1 % Mo)) are compared to YSt-355FR (0.126 % Mo). The YSt-355FR (0.1 % Mo) steel has shown greater strength properties compared to YSt-355FR (0.126 % Mo) up to 300 °C. The Finite Element Analysis (FEA) performed on the YSt-355FR (0.1 % Mo) structural steel column at elevated temperatures confirms: (i) conservative prediction of buckling strength by EC3, and (ii) the better performance of YSt-355FR (0.1 % Mo) column compared to YSt-355FR (0.126 % Mo) column up to 200 °C. The results indicate the needful incorporation of the strength reduction factor of cold-formed steel in all the fire design codes. Important observations were pointed out in the present study that can assist engineers and designers in developing high-performance FR steel structures.